2016
DOI: 10.1186/s12942-015-0028-2
|View full text |Cite
|
Sign up to set email alerts
|

The use of national administrative data to describe the spatial distribution of in-hospital mortality following stroke in France, 2008–2011

Abstract: Background: In the context of implementing the National Stroke Plan in France, a spatial approach was used to measure inequalities in this disease. Using the national PMSI-MCO databases, we analyzed the in-hospital prevalence of stroke and established a map of in-hospital mortality rates with regard to the socio-demographic structure of the country. Methods:The principal characteristics of patients identified according to ICD10 codes relative to stroke (in accordance with earlier validation work) were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Our cluster analysis identified six unique residential clusters for this study as shown in the dendrogram (Figure 1); the number of clusters formed is consistent with other studies using similar methodology to examine neighborhood-associated SES. 38,39 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our cluster analysis identified six unique residential clusters for this study as shown in the dendrogram (Figure 1); the number of clusters formed is consistent with other studies using similar methodology to examine neighborhood-associated SES. 38,39 …”
Section: Resultsmentioning
confidence: 99%
“…25,38,39 Using PCA, researchers mathematically determine the most important factors representing the greatest variability in the geographic area. However, the cut-off for determining the importance of the factor components can be arbitrary.…”
Section: Discussionmentioning
confidence: 99%
“…Data linkage provides the opportunity to identify prior stroke, which is not possible with unlinked administrative data [37]. We recommend at least a 10-year look-back period to maximise the accuracy of estimates for incident and recurrent stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Our cluster analysis identified six unique residential clusters for this study as shown in the dendrogram ( Figure 1); the number of clusters formed is consistent with other studies using similar methodology to examine neighborhood-associated SES. 38,39 In the dendrogram, the outer ring is made up of 444 individual leaves, with each leaf representing a Census block group. Each leaf was also given a color, and the colors correspond to the cluster designation.…”
Section: Resultsmentioning
confidence: 99%
“…A handful of studies have also used combinations of PCA and hierarchical clustering to help define neighborhood SES. 25,38,39 Using PCA, researchers mathematically determine the most important factors representing the greatest variability in the geographic area. However, the cut-off for determining the importance of the factor components can be arbitrary.…”
Section: Discussionmentioning
confidence: 99%